2002
DOI: 10.1007/s00442-001-0824-1
|View full text |Cite
|
Sign up to set email alerts
|

The ecological role of orientation in tropical convolvulaceous flowers

Abstract: Flowers of Ipomoea pes-caprae and Merremia borneensis show a preferred orientation, pointing in the general direction of the sun but not exactly tracking the sun. They demonstrated no diurnal heliotropism but strong seasonal heliotropism. The possible effects of this non-random orientation on the heat balance of the flower and the possible consequences on pollination were studied by measuring gynoecium temperature and insect visitation. Differently treated flowers were used to measure gynoecia temperature alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
16

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 14 publications
1
46
0
16
Order By: Relevance
“…The adaptive signiWcance of Xower orientation has been investigated in terms of pollinator attraction (Kevan 1975;Kudo 1995;Huang et al 2002;Patino et al 2002;Ushimaru et al 2006), but few studies have focused on the eYciency of pollen transfer (e.g., Tadey and Aizen 2001;Ushimaru et al 2006). We found that Xower angle strongly inXuenced pollinator behaviors and consequent pollen transfer in a zygomorphic species, suggesting the importance of Xower orientation in specialized pollination systems.…”
Section: Discussionmentioning
confidence: 85%
“…The adaptive signiWcance of Xower orientation has been investigated in terms of pollinator attraction (Kevan 1975;Kudo 1995;Huang et al 2002;Patino et al 2002;Ushimaru et al 2006), but few studies have focused on the eYciency of pollen transfer (e.g., Tadey and Aizen 2001;Ushimaru et al 2006). We found that Xower angle strongly inXuenced pollinator behaviors and consequent pollen transfer in a zygomorphic species, suggesting the importance of Xower orientation in specialized pollination systems.…”
Section: Discussionmentioning
confidence: 85%
“…For example, in a rainy environment, it may be optimal for a plant to have its flowers pointing downwards in order to avoid flooding out the nectar (Aizen 2003;Tadey & Aizen 2001). Similarly, heliotropic plants move their flowers to face towards the sun throughout the day, which may be an important strategy for pollinator attraction or floral development in cold climates (Kevan 1975;Kudo 1995;Patiño et al 2002). Furthermore, field experiments have demonstrated that unusual floral orientation may have an effect upon pollinator landing behaviour (Ushimaru & Hyodo 2005) and pollination success (Ushimaru et al 2009), and it is known that floral orientation can be used as a cue by honeybees (Lamb & Wells 1995) and beetles (Dafni & Potts 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Insects may warm up passively by basking in the sun but large bees can also warm up actively through shivering thermogenesis, contracting the flight muscles to produce metabolic heat (Heinrich 1979). Insects may also profit from flowers whose temperature is higher than that of the ambient air (Herrera 1995;Lack 1976;Patino et al 2002;Totland 1996). Above-ambient floral temperature may result from heliotropic movement of concave flowers (Galen and Stanton 2003;Kevan 1975;Orueta 2002;Patino et al 2002;Totland 1996) or floral metabolic thermogenesis (Dieringer et al 1999;Jewell et al 1994;Patino et al 2000;Seymour et al 2003).…”
Section: Introductionmentioning
confidence: 98%